2014
DOI: 10.1093/ehjci/jet287
|View full text |Cite
|
Sign up to set email alerts
|

Major congenital coronary artery anomalies in a paediatric and adult population: a prospective echocardiographic study

Abstract: MCA is a rare condition. TTE appears to be a potentially useful modality for the initial screening of MCA in adults and children, provided special attention is paid to coronary artery analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…Angelini et al [18] reports a frequency of high risk anomalous coronaries as high as 0.44% in a population of middle and high school healthy volunteers. As described in other studies [1][2][3][4][5][6][18][19][20], we also found that interarterial AORCA was 3 times more frequent than AOLCA.…”
Section: Discussionsupporting
confidence: 90%
“…Angelini et al [18] reports a frequency of high risk anomalous coronaries as high as 0.44% in a population of middle and high school healthy volunteers. As described in other studies [1][2][3][4][5][6][18][19][20], we also found that interarterial AORCA was 3 times more frequent than AOLCA.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have attempted to quantify this value, with estimates ranging between 0.1% and 1.0% in both the adult and pediatric populations. [1][2][3][4][5][6][7] The wide difference in prevalence rates is likely due to RCA courses between aorta and pulmonary artery (interarterial) 4. Single LMCA arises from left sinus of Valsalva and bifurcates into the left anterior descending coronary and left circumflex coronary arteries.…”
Section: Section I: Background Prevalencementioning
confidence: 99%
“…The incidence of congenital coronary anomalies ranges between 1 and 5% undergoing coronary angiography and 0.3% in autopsy series. [1,2] Echocardiographic studies in pediatric population reported an incidence of 0.3%. [3] Potentially serious coronary anomalies include ectopic coronary origin from the pulmonary artery, ectopic coronary origin from the opposite sinus, single coronary artery, and coronary fistula.…”
Section: Discussionmentioning
confidence: 99%